Perancangan Dashboard Visualisasi Data Kesehatan Ibu dan Anak di Dinas Kesehatan Kabupaten Jember - Putri, Etania Febry Kirana; Ramani, Andrei (UPT Percetakan dan Penerbitan Universitas Jember, 2024)
The amount of data generated is a challenge for agencies in the health sector to quickly analyze needs and interventions. The management and presentation of data carried out by the Jember District Health Office has not yet found an optimal method to present a lot of data into easily understood health information. This study aims to design a health data visualization dashboard using Microsoft Excel to assist in data management and facilitate policy formulation. The method used is research and development (R&D) with a visual data mining (VDM) model. The results showed that the data used for visualization was the MCH data of Jember Regency in 2021. The resulting dashboard consists of 4 maternal health dashboards and 5 child health dashboards. Verification of dashboard results shows that the dashboard is 100% functional, so it is accepted by the user. Dashboard testing using the User Experience Questionnaire (UEQ) has an average of positive evaluation results. Future researchers are expected to develop the types of data and visualization tools used in designing dashboards.